Preparation of Nickel Nanocatalysts and Application to the Hydrodechlorination of 3-Chlorophenol under Liquid Phase. (4th March 2021) - Co, Thanh Thien; Tran, Thi Kim Anh; Doan, Thi Huong Ly; Diep, Thi Duyen
Abstract : Nickel nanoparticles were successfully synthesized via the reduction of nickel salt using ethylene glycol (EG) and sodium borohydride (NaBH4 ) as reducing agents. These nickel nanoparticles were then loaded on the supports as Ni-X (X = vanadium phosphorus oxides (VPO), TiO2, and ZnO) in high loading yield. The optical properties of these catalysts were characterized by UV-vis spectroscopy, the structure of Ni-X was studied by powder X-ray diffraction (PXRD), the distribution of Ni particles in X was studied by transmission electron microscopy (TEM), and the specific surface area of Ni-X was evaluated by N2 adsorption isotherm analysis at 77 K. All results corroborated the loading process. Indeed, TEM image indicated that the nickel nanoparticles size is in the range of 14 ÷ 16 nm and fully loaded into X. The activities of these catalysts were performed on the hydrodechlorination of 3-chlorophenol in the presence of sodium hydroxide as base at atmospheric pressure and at RT. The results showed that Ni-X exhibited high activities up to 98% within 90 min in the case of Ni-ZnO catalyst.